Quality indicators for rural surgical and obstetrical care: A modified Delphi consensus study - Anshu Parajulee; Abdo Souraya; Nancy Humber; Sean Ebert; Kim Williams; Tom Skinner; Jude Kornelsen (PLoS ONE, 2025)
Objective To identify contextually relevant indicators to measure the quality of surgical and obstetrical care in low-volume rural hospitals using a consensus-based methodology. Methods A modified Delphi process was implemented in which participants were asked to rate the priority of proposed evaluation metrics over two rounds. Two Delphi surveys were electronically administered in 2019, approximately one month apart. Fifty-one health care professionals from across Canada, including rural proceduralists and quality improvement experts, were invited to participate. All quality measures in the first round were proposed by the study team. The second round included measures that did not reach consensus in the first round and measures suggested by respondents during the first round. Results Thirty individuals participated in Round 1 (59% response rate). Of the 30 respondents from Round 1, 23 participated in Round 2 (77% response rate). 115 of 177 proposed measures (65%) reached positive consensus in Round 1 or 2. Expert participants agreed that these measures should be prioritized/included when evaluating surgical and/or obstetrical quality in rural hospitals. No measure reached negative consensus in either round. Open-text comments offered practical guidance on how to interpret and use surgical and obstetrical quality data within a rural context. Many respondents believed that rare adverse outcomes have low relevance at rural hospitals where volumes are low, procedures are almost all lower complexity day cases (Cesarean section being the major exception), and patients are typically healthy. Conclusion The modified Delphi process resulted in the identification of surgical and obstetrical quality indicators that are contextually embedded in the realities of rural practice. The methodology allowed for the consideration of factors often overlooked by normative urban-based approaches, including team-based care characteristic of rural hospitals and limited access to specialist care and imaging services.